Novel Coumarin Derivatives as Potential Urease Inhibitors for Kidney Stone Prevention and Antiulcer Therapy: From Synthesis to In Vivo Evaluation - Kiran Shahzadi; Syed Majid Bukhari; Asma Zaidi; Tanveer A. Wani; Muhammad Saeed Jan; Seema Zargar; Umer Rashid; Umar Farooq; Aneela Khushal; Sara Khan (Pharmaceuticals, 2023)
The presence of ammonium ions in urine, along with basic pH in the presence of urease-producing bacteria, promotes the production of struvite stones. This causes renal malfunction, which is manifested by symptoms such as fever, nausea, vomiting, and blood in the urine. The involvement of urease in stone formation makes it a good target for finding urease enzyme inhibitors, which have the potential to be developed as lead drugs against kidney stones in the future. The documented ethnopharmacology of coumarin 2-one against bacterial, fungal and viral strains encouraged us to synthesize new derivatives of coumarins by reacting aromatic aldehydes with 4-aminocoumarin. The synthesized compounds (2a to 11a) were evaluated for their antimicrobial, in vitro, and in silico properties against the urease enzyme. The study also covers in vivo determination of the synthesized compounds with respect to different types of induced ulcers. The molecular docking study along with extended MD simulations (100 ns each) and MMPBSA study confirmed the potential inhibitory candidates as evident from computed ∆Gbind (3a = −11.62 and 5a = −12.08 Kcal/mol) against the urease enzyme. The in silico analyses were augmented by an enzymatic assay, which revealed that compounds 3a and 5a had strong inhibitory action, with IC50 of 0.412 µM (64.0% inhibition) and 0.322 µM (77.7% inhibition), respectively, compared to standard (Thiourea) with 82% inhibition at 0.14 µM. Moreover, the most active compound, 5a, was further tested in vivo for antiulcer activity by different types of induced ulcers, including pyloric ligation-, ethanol-, aspirin-, and histamine-induced ulcers. Compound 5a effectively reduced gastric acidity, lipid peroxidation, and ulceration in a rat model while also inhibiting gastric ATPase activity, which makes it a promising candidate for ulcer treatment. As a result of the current research, 3a and 5a may be used as new molecules for developing potent urease inhibitors. Additionally, the compound 3a showed antibacterial activity against Staphylococcus aureus and Salmonella typhimurium, with zones of inhibition of 41 ± 0.9 mm and 35 ± 0.9 mm, respectively. Compound 7a showed antibacterial activity against Staphylococcus aureus and Salmonella typhimurium, with zones of inhibition of 30 ± 0.8 mm and 42 ± 0.8 mm, respectively. These results prove that the synthesized compounds also possess good antibacterial potential against Gram-positive and Gram-negative bacterial strains.